PENGARUH PROFITABILITAS, LIKUIDITAS, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN: - - Ardiyah Azizah; Retnaningdiah, Dian - (Journal Competency of Business, 2024)
Abstract Background: A company is an institution or organization whose mission is to provide goods and services to maximize profits. Every company management wants their company to remain sustainable; therefore, it always tries to find strategies to achieve its goals. Company value is central to investors' decisions to invest in a company. The higher the company value, the higher the company's image. This company's high and low value cannot be separated from the various factors that influence it. Several factors can affect the value of a company, including profitability, capital structure, and liquidity. Aim of the Study: The study aimed to test the effect of profitability, liquidity, and capital structure on company value partially and simultaneously. Research Method: This quantitative research used secondary data from the Indonesia Stock Exchange. The population in this study included food and beverage sector companies listed on the IDX for 2020-2022. The sampling method used purposive sampling. The sample in this study was 31 companies for three years, and after outlier data, the total sample was 93. The data analysis technique used was descriptive statistics and Multiple Linear Regression using SPSS software version 26 with a significance level of 5%. Findings: The data analysis showed that the capital structure variable partially affects the company value. Meanwhile, the liquidity and profitability variables partially do not affect the company value. The profitability, liquidity, and capital structure variables simultaneously jeopardize the company's value. Keywords: Profitability, Liquidity, Capital Structure, Company Value.